Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Self-adhesive aluminophosphate-enabled multifunctional cellulose paper for high-performance, flame-retardant, and water-resistant triboelectric nanogenerators - Haoran Liu; Gang Zhao; Mingyue Li; Yinyin Wang; Qiulu Liu; Nanhua Chen; Zhaoxing Lin; Xiangfang Peng; Tingjie Chen (Chemical Engineering Journal, 2026)

Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

Coupling of venting and composite porous media on overpressure and quenching characteristics of HCNG explosions in tunnel - Zhenzhen Zhao; Yuntao Liang; Fuchao Tian; Haoran Zhao; Baolong Guo; Lin Wang (Tunnelling and Underground Space Technology, 2026)

Sustainable nitrogen-doped biochar derived from dual agricultural wastes for water treatment - Feihuang Lin; Jiewen Wu; Zhantu Zhang; Yuyuan Zhang; Chenlong Niu; Jifeng Cui; Menglei Chang; Haoran Yuan; Huawen Hu (Journal of Water Process Engineering, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

New critical nitrogen dilution curve for brewing sorghum in Southwestern China based on a Bayesian hierarchical model - Lin Yang; Yifan Zhou; Zilong Bai; Haoran Zhang; Jie Wang (European Journal of Agronomy, 2026)

Tailored nanocavities in an interpenetrated metal-organic framework for enhanced removal and detection of aluminum ions in rare earth wastewater - Haoran Li; Yanan Wang; Wentao Pan; Qiang Wang; Longsheng Yang; Huiyin Lin; Jingwen Chen; Shixia Chen; Zhenyu Zhou; Jun Wang (Chemical Engineering Journal, 2026)

Cu–nanosheet wrapped plant fiber sponge with tip-enhanced electric field for self–powered triboelectric gesture recognition via convolutional neural network - Yinyin Wang; Jianhao Yang; Wuyi Li; Gang Zhao; Qiulu Liu; Haoran Liu; Zhaoxing Lin; Lihong Xu; Li Huang; Xiangfang Peng; Binghui Wu; Tingjie Chen (Chemical Engineering Journal, 2026)

Fine-scale mapping of built-environment carbon emissions: A multi-source data fusion and explainable machine learning framework for high-density urban regions - Ge Shi; Haoran Tang; Wei Wang; Chuang Chen; Jiantao Shi; Bo Wang; Lin Sun (Building and Environment, 2026)

Physics-informed model predictive control for active heave compensation of electrical winches - Ruhua Zhang; Wenhua Li; Shanying Lin; Gen Li; Haoran Ye; Xingjian Lou (Ocean Engineering, 2026)

Study on sliding wear mechanism and performance degradation of polyurethane-coated HMPE ropes in sheave systems for deep-sea winch - Yiqun Lin; Wenhua Li; Gen Li; Shanying Lin; Haoran Ye; Hangyu Li (Ocean Engineering, 2026)

Vortex-induced vibration of subsea rigid jumpers conveying gas–liquid two-phase flow - Guangzhao Li; Wenhua Li; Shanying Lin; Haoran Ye; Gen Li (Ocean Engineering, 2026)

Mechanisms of heavy metal immobilization and transformation during co-pyrolysis of pig manure with typical organic solid wastes - Fengxiao Zhao; Danni Li; Hongyuan Chen; Xianhai Zeng; Rui Shan; Lu Lin; Haoran Yuan; Yong Chen (Journal of Hazardous Materials, 2026)

Design and optimization of an autothermal solid oxide electrolysis cell reactor for efficient and economical solar-driven carbon dioxide reduction - Zihan Lin; Junjie Hou; Haoran Li; Qi Xia; Jiale Long; Zhouxin Pan; Muhammad Sajid Khan; Chen Chen (Journal of Cleaner Production, 2026)

Formation of digestive enzyme coronas in inulin-hydroxypropyl-β-cyclodextrin nanoparticles: Size-dependent modulation of protease activity and curcumin release - Peihua Yuan; Qianzhu Lin; Haoran Fan; Zhengyu Jin; Hangyan Ji; Chao Qiu (Food Bioscience, 2026)

Dynamically bridged and compressible TPU aerogel with multi-dimensional carbon synergy for high-performance triboelectric sensing in diabetic foot monitoring - Tingjie Chen; Bingqiang Yan; Gang Zhao; Qiulu Liu; Yinyin Wang; Haoran Liu; Nanhua Chen; Zhaoxing Lin; Xiangfang Peng (Chemical Engineering Journal, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

A predictive frequency-selected method for optimizing microwave heating with a solid-state system - Haoran Wu; Jiuzou Zhang; Lin Wang; Dezhi Gou; Zhengming Tang (Journal of Food Engineering, 2026)

Tailoring charge redistribution to suppress lattice oxygen release in Ni-rich single–crystal cathodes - Qianqian Jiang; Zhencheng Huang; Xi Chen; Tao Huang; Jingguo Gao; Yingqi Xu; Jinqi Dong; Wei Zeng; Haoran Wei; Feifan Wan; Lin Chen; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Role of cholecystokinin (CCK) in reproductive regulation of female mandarin fish (Siniperca chuatsi) - Shuang Liu; Chongwei Wang; Yuting Wang; Chaowei Li; Jinmeng Teng; Suhan Peng; Jiaqi Lin; Jin Zhang; Haoran Lin; Linqiang Han; Ju Hu; Shuisheng Li; et al. (Aquaculture, 2026)

Nonlinear modeling and dynamic analysis of wireline riser tensioners for deep-sea mining risers - Yan Li; Wenhua Li; Baoyun Qi; Haoran Ye; Shanying Lin; Gen Li (Ocean Engineering, 2026)

Multi-Objective Optimization Design of Cylindrical FPSO Mooring System Based on KAN Surrogate Model and NSGA-III Algorithm - Wenhua Li; Mingshuai Yu; Huoping Wang; Haoran Ye; Liuzhong Cao; Shanying Lin (Journal of Marine Science and Engineering, 2026)
Cylindrical floating production storage and offloading (FPSO) units are advancing into deeper waters. Overcoming the severe challenges posed by complex deepwater environments requires the design of mooring systems that balance economic efficiency and mooring performance. This paper proposes an innovative optimization method for cylindrical FPSO mooring systems, combining the Kolmogorov–Arnold Network (KAN) with the Non-dominated Sorting Genetic Algorithm III (NSGA-III). Configuration samples are generated within predefined design variable ranges using Latin Hypercube Sampling (LHS), followed by time-domain global response simulations using OrcaFlex (version 11.3) software. A KAN surrogate model is constructed to predict the dynamic responses of the mooring system. Finally, the NSGA-III algorithm is employed for multi-objective optimization to obtain the Pareto optimal set, aiming to minimize mooring costs, maximum tension, fatigue damage, and platform offset. The results demonstrate that, compared to traditional optimization methods, the combination of KAN and NSGA-III exhibits superior prediction accuracy and generalization capabilities. The optimized configurations significantly outperform the original design in both mooring performance and economic costs. Specifically, the most economical scheme reduces mooring costs by 20.73%, the minimum tension scheme decreases mooring line tension by 46.75%, and the minimum displacement scheme reduces platform offset by 30.88%.

Study on the characteristics and prediction model of gas-liquid two-phase slug flow in subsea jumper - Wenrui Song; Wenhua Li; Shanying Lin; Haoran Ye; Gen Li (Ocean Engineering, 2026)

Structural vibration analysis and safety assessment of centrifuges under hypergravity environments - Chengpeng Hong; Guanwen Liang; Li Bi; Haoran Fu; Zizhuang Yan; Kuigen Lin; Yunmin Chen (Engineering Structures, 2026)

A biomimetic molecular ‘tailor’ hydrogen bonds and ‘guide’ crystal planes to achieve dendritic-free zinc anodes - Haoran Lang; Chunyuan Xiong; Yufan Chen; Qiaoji Zheng; Yu Huo; Heng Zhang; Haoqi Yang; Dunmin Lin (Chemical Engineering Journal, 2026)

A hybrid deep learning and empirical model for short-term spatio-temporal ZTD forecasting for China - Xiongwei Ma; Haoran Huang; Qi Zhang; Bao Zhang; Qingzhi Zhao; Xiaohu Lin; Yunzheng Huang; Yiyang Zhao; Yibin Yao (Journal of Geodesy, 2026)

The Fight is not Over: Sustained Vigilance Against Schistosomiasis Needing in China - Haoran Zhong; Yamei Jin; Jiaojiao Lin (Acta Parasitologica, 2026)

Membrane aerated biofilm reactor for largely enhanced nitrogen removal in low carbon/nitrogen ratio municipal wastewater: integrating nitrification, partial denitrification, and anammox - Xiwei Cao; Lin Zhang; Haoran Tu; Ting Li; Guofeng Wang; Ling Xiao; Yupeng Zhang; Peng Liu; Yi Li; Jiaye Li; Xinglin Li; Boyang Hu; et al. (Bioresource Technology, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Integrating biodiversity hotspots, ecological gradients, and ecosystem services for transboundary conservation in the Gaoligong Mountains - Zhongde Huang; Qiying Wang; Jie Wang; Zhou Fang; Lin Wang; Maroof Ali; Zhangqian Yang; Haoran Chen; Shi Xue; Qin Zhou; Changgao Cheng; Feiling Yang; et al. (Conservation Biology, 2026)
Expanding transboundary protected areas is crucial to biodiversity conservation and maintenance of ecosystem services. Quantifying border gradients of species richness is essential to aligning ecological and management boundaries to enable the gradual integration of biodiversity hotspots in conservation strategies that include cross‐border areas that buffer the effects of extensive infrastructure. For the China–Myanmar border region (Gaoligong Mountains), we developed a conservation plan based on threatened species, ecosystem services, border gradient characteristics (i.e., spatial changes in ecological variables with increasing distance from a boundary), and ecological connectivity of protected areas. Although 20.2% of existing protected areas were in the north, 27.7% of identified priority conservation areas were outside these protected areas and only 2.93% were protected. Threatened plant and animal richness exhibited a positive spatial correlation (coefficient = 0.12), but their richness hotspots were spatially mismatched. The richness of threatened species was positively correlated with carbon storage and soil retention, but negatively correlated with water retention. In contrast, threatened animal diversity showed the opposite pattern. Threatened species richness decreased as distance from the border increased (strong linear relationship, R 2 = 0.95 for plants and 0.59 for animals). Based on our results, we propose an ecological gradient–based conservation strategy that prioritizes areas where the richness of threatened species overlaps in the central and southern regions and that protects biodiversity hotspots and creates corridors. The framework is applicable to other transboundary regions and supports global biodiversity conventions.

Will carbon emissions trading promote carbon neutral technological innovation in China? An analysis combining DID and generalized random forest - Jingru Li; Haoran Lin; Yanbin Cheng; Huanyu Wu (Environment, Development and Sustainability, 2026)

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Flow-induced vibration suppression of a square cylinder with Y-shaped jet configuration: Inspired by fish gill structures - Yiqun Lin; Wenhua Li; Gen Li; Fenghui Han; Shanying Lin; Haoran Ye (Ocean Engineering, 2026)

Modulation of viscosity, swallowability, and stability of starch-based thickener: The effect of konjac gum and xanthan gum - Haoran Fan; Lin Sun; Xiaodan Liu; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2026)

Immunological Characteristics of Triploid Grass Carp (Ctenopharyngodon idella) and evaluation of its phagocytosis in the macrophages of head kidney - Xiaoman Huang; Zixuan E; Hao Yang; Guihong Lai; Shuang Liu; Shujia Liao; Jiaqi Lin; Siyi Liu; Chen Long; Haoran Lin; Danqi Lu; Shuisheng Li; et al. (Fish & Shellfish Immunology, 2026)

Corrigendum to “Genome-wide identification, characterization, and expression analysis of scavenger receptor genes in orange-spotted grouper (Epinephelus coioides)” [Fish Shellfish Immunol. 167 (2025) 110671] - Feirong Yuan; Jiayao Wu; Siyi Liu; Yaorong Wang; Zhenjiang Zou; Yanhua Huang; Jinhui Wu; Haoran Lin; Shuisheng Li; Yong Zhang; Danqi Lu (Fish & Shellfish Immunology, 2026)

The formation of autophagosomes in the development process of rice endosperm is affected by endogenous ascorbic acid - Le Yu; Mengwei Chen; Haoran Yan; Zeliang Ouyang; Xinyu Liu; Sitong Lin; Yixuan Tang; Zhipeng Xu; Chunyu Liu; Peiyi Chen; Liping Zhou; Yonghai Liu (Acta Physiologiae Plantarum, 2026)

Fat body specific ABCG3 accounts for xenobiotic tolerance and is regulated by the homeobox transcription factor Bcd in Spodoptera litura - Lin Liang; Long Jin; Furong Mao; Chengcheng Fan; Haoran Kong; Zixin Zhang; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Flow-induced vibration and stress prediction of subsea M-shaped jumpers under multiphase flow - Guangzhao Li; Wenhua Li; Shanying Lin; Haoran Ye; Gen Li (Ocean Engineering, 2025)

Color-categorized microplastics in rivers and lakes: Global distribution, driving mechanisms, and ecological risks unveiled by interpretable machine learning - Tianqi Jiang; Guangshuo Chai; Qiong Guo; Haoran Peng; Yuexia Guo; Xiaohui Zhang; Yan Lin; Hongyang Cui; Xiaoyu Cui; Yindong Tong (Journal of Environmental Chemical Engineering, 2025)

Genome-wide identification, characterization, and expression analysis of scavenger receptor genes in orange-spotted grouper (Epinephelus coioides) - Feirong Yuan; Jiayao Wu; Siyi Liu; Yaorong Wang; Zhenjiang Zou; Yanhua Huang; Jinhui Wu; Haoran Lin; Shuisheng Li; Yong Zhang; Danqi Lu (Fish & Shellfish Immunology, 2025)

Tri-modal fibrous electronic skin enabling thermal sensing, electrophysiological monitoring, and directional moisture transport - Yidong Peng; Xi Lin; Haoran Liu; Jiancheng Dong; Yunpeng Huang; Lailai Qin; Yanqing Gu; Tianxi Liu (Chemical Engineering Journal, 2025)

Fe/Mn/Zr ternary electrode facilitates ultra-low-resistance electrocatalysis for closed-loop electrochemical removal of heavy metals from industrial wastewater - Shaoying Lin; Xinyu Liu; Huiqiang Ma; Yanzhuang Liu; Yameng Wang; Haoran Liu; Bo Wang; Yihua Li; Changfei Gao (Chemical Engineering Journal, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Quantitative evaluation method for the winding package deformation of non-metallic armored CTD cable on the multi-layer winch - Shanying Lin; Zehua Li; Wenhua Li; Haoran Ye; Lei Hong; Fei Wang (Ocean Engineering, 2025)

Quantification of shear deformation in reinforced concrete beams: An approach integrating arch action and decoupling methodologies - Haoran Lin; Bing Li (Engineering Structures, 2025)

Breaking the monopoly of the Zn(002): Phosphoryl-heterocyclic co-adsorption to promote preferential exposure of Zn(101) crystal plane for dendrite-free Zn metal anodes - Haoran Lang; Chao Li; Jingxin Zhao; Chunyuan Xiong; Lieyuan Zhang; Yijia Luo; Qiaoji Zheng; Xin Tan; Hong Fu; Bingang Xu; Dunmin Lin (Chemical Engineering Journal, 2025)

Improved biosynthesis of lactulose by a novel thermostable cellobiose-2-epimerase generated through semi-rational mutagenesis - Chenggang Zhong; Weijian Ding; Haoran Lin; Jin Huang (World Journal of Microbiology and Biotechnology, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Intelligent prediction of food waste compost maturity using machine learning based on rapid detection process metrics - Zhonghao He; Jing Tang; Xiangyu Peng; Jing He; Haoran Dong; Leyuan Fang; Lin Tang (Journal of Cleaner Production, 2025)

Fatigue performance of CFRP-strengthened steel pipes with semi-elliptical surface cracks - Tao Chen; Zhuxuan Li; Xiang-Lin Gu; Zhigang Xiao; Wensu Chen; Haoran Zuo (Engineering Structures, 2025)

Regulating the coordination distance of solvation structure for high-performance aqueous zinc ion batteries - Yijia Luo; Chao Li; Lieyuan Zhang; Xin Tan; Yi Yang; Bin Xie; Dandan Zhang; Haoran Lang; Xingyu Chen; Xuemei He; Qiaoji Zheng; Xinqiao Wu; et al. (Chemical Engineering Journal, 2025)

Hierarchical porous TPU@CNT sponge for high-performance triboelectric nanogenerators via dual contact electrification and self-powered sensing applications - Yinyin Wang; Bingqiang Yan; Yinyun Zhou; Gang Zhao; Qiulu Liu; Haoran Liu; Zhaoxing Lin; Xiangfang Peng; Tingjie Chen (Chemical Engineering Journal, 2025)

Enzymatic resistance of starch-polyphenol inclusion complexes: polyphenol inhibition and structural changes during in vitro digestion - Haoran Fan; Lin Sun; Xu Yao; Yangyang Wen; Xuesong Xiang; Hongyan Li; Jing Wang; Baoguo Sun (Carbohydrate Polymers, 2025)

Transcriptome analysis revealed that largemouth bass (Micropterus salmoides) may mobilize liver lipid metabolism to provide energy for adaptation to hypertonic stress - Xinxin Wang; Chaoyue Deng; Wenyan Lin; Huapeng Chen; Haoran Yu; Shukui Sun; Junlong Sun; Jian Luo; Feibiao Song (Aquaculture, 2025)

Multi-scale stabilization of cobalt-free lithium-rich layered oxides via dual redox modulation for high-energy and long-life cathodes - Ning Wang; Chengliang Lin; Shengrui Cui; Haoran Li; Yukui Wang; Mingzhu Yang; Wenchao Yan; Wei Liu; Yongcheng Jin (Chemical Engineering Journal, 2025)

3-Indolepropionic acid confers PXR-p53 binding to mitigate deoxynivalenol-induced hepatocyte apoptosis - Yue Feng; Zishen Lin; Haoran Wang; Zhaoyue Men; Jiakun Shen; Xi Ma (Science China Life Sciences, 2025)

Multiomics reveals the impact of microplastics and di-n-octyl phthalate on hormone biosynthesis in cucumber - Haoran Zhuang; Yiwen Chu; Menglin Wang; Bo Liu; Bihua Chen; Ziyu Lin; Zhenxia Li (Physiology and Molecular Biology of Plants, 2025)

High-efficiency electrochemical desalination enabled by nanosheet-structured redox polymer for sustainable and versatile water treatment - Peipei Zhang; Haoran Xu; Jun Yang; Minjie Shi; Yuqing Lin (Water Research, 2025)

Characterization of CmXERICO gene regulating carotenoid accumulation and morphogenesis in Citrus maxima - Haoran Zhang; Jiaxing Zheng; Nan Bai; Xiaoqin Jin; Wenbo Lin; Changchun Wang (Genetic Resources and Crop Evolution, 2025)

Seismic response of the composite bucket foundation supported offshore wind turbines under marine environmental loadings - Wei Cheng; Yikang Wang; Ming Li; Guangwei Xu; Haoran Lin; Panpan Shen (Marine Georesources & Geotechnology, 2025)

The formation of a hybrid fish derived from Labeo rohita ♀ × Cyprinus carpio ♂ and exhibiting stronger low temperature tolerance - Jiali Lin; Haoran Zhang; Jietao Wang; Bing Fu; Zexun Zhou; Wuhui Li; Huirong Yang; Shaojun Liu (Aquaculture, 2025)

An adaptive control method of non-metallic armoured Optical-electrical cable winch system in Oceanographic Research Vessel based on three-dimensional laser scanning point cloud - Haoran Ye; Hongjie Guo; Wenhua Li; Shanying Lin; Gen Li; Lei Hong (Ocean Engineering, 2025)

Pyrolysis of pig waste from intensive farming operations: Kinetics, product distribution, and transformation of endogenous heavy metals - Fengxiao Zhao; Danni Li; Hongyuan Chen; Xianhai Zeng; Lu Lin; Haoran Yuan; Rui Shan; Yong Chen (Journal of Hazardous Materials, 2025)

HDAC9 Deficiency Upregulates cGMP-dependent Kinase II to Mitigate Neuronal Apoptosis in Ischemic Stroke - Haoran Lin; Yun Bei; Zexu Shen; Taofeng Wei; Yuyang Ge; Lingyan Yu; Huimin Xu; Wei He; Yunjian Dai; Difei Yao; Haibin Dai (Translational Stroke Research, 2025)

P2Y6R Inhibition Induces Microglial M2 Polarization by Promoting PINK1/Parkin-Dependent Mitophagy After Spinal Cord Injury - Jiezhao Lin; Yuanfang Sun; Haoran Huang; Cheng Yu; Wenhao Kuang; Yihan Wang; Lixin Zhu (Molecular Neurobiology, 2025)

Advancing dynamic reliability assessment of reservoir slopes using attention-based neural networks - Lin Wang; Kangjie Yang; Yang Zhou; Junzhi Liu; Haoran Hu (Bulletin of Engineering Geology and the Environment, 2025)

Dynamic Modeling and Experimental Validation of Shock Isolation Performance for Shipborne Stewart-Platform-Based Bumper - Yongqiang Tu; Haoran Zhang; Yintao Li; Wei Wang; Gang Lu; Hongwei Lin; Xinkai Chen; Yan Huang; Jianyu Fan (Journal of Marine Science and Engineering, 2025)
The Stewart-platform-based bumper plays a critical role in shipborne strap-down inertial navigation systems (SINSs), effectively mitigating shock-induced disturbances to ensure measurement accuracy. Dynamic modeling for the bumper under a huge impact is a key issue in predicting the shock isolation performance of the bumper. In this paper, the dynamic modeling of shock isolation performance for Stewart-platform-based bumpers under huge impacts is proposed and validated experimentally. Firstly, a model of a Stewart-platform-based bumper is established considering the geometric configuration and dynamic parameters of the bumper by calculating the Jacobian matrix, stiffness matrix, damping matrix and mass matrix. Secondly, an analytic simulation of the impact is presented based on the measured impact acceleration, and the impact force on the load is derived according to the non-displacement assumption in the impact stage. Then, the Lagrangian formulation was systematically applied to establish governing equations characterizing the six-degree-of-freedom (DOF) dynamics of the bumper, incorporating both inertial coupling effects and nonlinear shock energy dissipation mechanisms. Afterwards, dynamic equations were solved via the Runge–Kutta method to obtain the theoretical results. Finally, the proposed dynamic modeling and shock isolation performance analysis method was validated via impact experiments for the bumper.

Dietary spermine supplementation enhances growth, protein synthesis, and antioxidant capacity in hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Lina Geng; Chirun Lin; Guojian Pan; Yusen Yang; Lixing Wang; Shengming Huang; Zhiyu Zhou; Haoran Yin; Xiaoyi Wu (Aquaculture, 2025)

Identification of dietary protein utilization traits related SNPs and genes in brown-marbled grouper (Epinephelus fuscoguttatus) - Jin Zhang; Qinxi Dai; Yaorong Wang; Qianhao Wei; Cheng Peng; Yuqing Yang; Jinxiong Huang; Yanhua Huang; Jinhui Wu; Haoran Lin; Danqi Lu; Yong Zhang; et al. (Aquaculture, 2025)

Experimental and numerical investigation of flow pattern evolution and flow-induced vibrations in an M-shaped subsea jumper under gas-liquid two-phase flow conditions - Wenrui Song; Wenhua Li; Shanying Lin; Haoran Ye; Gen Li (Ocean Engineering, 2025)

Elastic and degradable cyclodextrin nanofibrous aerogel: Enhanced dynamic thermal management and broadband sound absorption - Jia-Xin Wang; Haoran Xu; Dong-Lin Guo; Meng-Meng Song; Ye-Tao Zhang; Bang-Jing Li; Sheng Zhang (Journal of Cleaner Production, 2025)

Insights into the kinetics of ethyl levulinate production from cellulosic biomass alcoholysis under high solid content - Haoran Wu; Xin Wang; Jingyang Zhang; Zhen Ma; Yucheng Lin; Chun Chang; Xiuli Han (Biomass and Bioenergy, 2025)

Real-Time Fault Diagnosis of Mooring Chain Jack Hydraulic System Based on Multi-Scale Feature Fusion Under Diverse Operating Conditions - Yujia Liu; Wenhua Li; Haoran Ye; Shanying Lin; Lei Hong (Journal of Marine Science and Engineering, 2025)
The condition monitoring of mooring equipment is an important engineering reliability issue during the operation of a floating production storage and offloading unit (FPSO). The chain jack (CJ) is the key equipment for powering the mooring chain in a spread mooring system. Under complex and dynamic marine operating conditions, different severity faults in the CJ hydraulic system display distinct time-scale characteristics. Hence, this paper proposes a real-time fault diagnosis method of the CJ hydraulic system based on multi-scale feature fusion. Firstly, the model incorporates a convolutional neural network (CNN) layer to extract localized spatial features from multivariate time-series data, effectively identifying fault patterns over the associated short intervals. Subsequently, the bidirectional long short-term memory (BiLSTM) layer is introduced to construct a dynamic temporal model to comprehensively capture the evolution of the fault severity. Finally, a multi-scale global attention mechanism (GAM) emphasizes persistent fault behaviors across time scales, dynamically prioritizing relevant features to improve diagnostic accuracy and model interpretability. The study results indicate that the proposed model’s accuracy improves by 7.36% over the CNN-GAM for 11 failure modes, up to 99.34%. This study contributes to the safe operation of an FPSO by guiding monitoring CJ operations under different load conditions.

Horizontally oriented 2D skin structures on fiber interface for long-life flexible energy storage devices - Guangyu Fang; Xiaorui Ma; Rong Hu; Jiao Dai; Haoran Tian; Lin Li; Weilin Xu; Yonggang Yao; Jun Wan (Chemical Engineering Journal, 2025)

Modifying buried heterogeneous contacts to promote efficient carrier extraction for efficient perovskite solar cells - Lei Gu; Jiacheng Su; Ruiqian Chen; Haoran Deng; Lei Zhao; Chunming Yang; Lin Song (Chemical Engineering Journal, 2025)

Changes in fertility and microbial communities of red soil and their contribution to crop yield following long-term different fertilization - Haoran Mao; Ke Leng; Xinyi Chen; Jie Zhang; Kailou Liu; Yongxin Lin; Xingjia Xiang; Jia Liu (Journal of Soils and Sediments, 2025)

In-situ testing and analysis of aerodynamic characteristics of tomato plants in large-span arched greenhouse - Bo Lin; Haoran Song; Guiyuan Liu; Zihao Qi; Renhui Guan; Min Wei; Guanshan Zhang; Yanyan Jia; Shaojie Wang (Computers and Electronics in Agriculture, 2025)

Experimental investigations in the effect of passive gyro stabilizers on the pitch motion of a semi-submersible floating wind turbine - Junlei Wang; Haoran Li; Jisheng Zhang; Dawei Guan; Xiangfeng Lin; Hao Chen (Ocean Engineering, 2025)

Reutilizing waste photovoltaic plastics by pyrolysis: Dynamics, thermodynamics, mechanisms, products, and optimization - Xin Chen; Jingyong Liu; Ziting Lin; Jinwen Lu; Liangzhong Li; Yan Chen; Fatih Evrendilek; Chenyu Yang; Haoran Yuan; Yao He (Fuel, 2025)

Carbon dots alleviate photoinhibition and enhance photosynthesis in Chlorella pyrenoidosa - Fengqiong Chen; Na Yang; Xiaoman Huang; Junjie Lin; Haoran Zhang; Xuejie Zhang; Yingliang Liu; Wei Li; Bingfu Lei (Chemical Engineering Journal, 2025)

Alcoholysis of High-Solid xylose residue for methyl levulinate preparation and its kinetics - Zhen Ma; Jingyang Zhang; Yucheng Lin; Xiuli Han; Haoran Wu; Chunbao Xu; Chun Chang (Bioresource Technology, 2025)

Novel approach to quantitative risk assessment of reservoir landslides using a hybrid CNN-LSTM model - Lin Wang; Kangjie Yang; Chongzhi Wu; Yang Zhou; Junzhi Liu; Haoran Hu (Landslides, 2025)

Atmosphere-dependent pyrolytic transformability of glass fiber/epoxy resin composites in waste wind turbine blades - Siqi Chen; Jingyong Liu; Ziting Lin; Sen Lin; Liangzhong Li; Yan Chen; Fatih Evrendilek; Weixin Li; Wenxiao Huang; Chenyu Yang; Haoran Yuan; Yao He; et al. (Chemical Engineering Journal, 2025)

Characteristics of Tylvalosin Tartrate Enteric Amorphous Pellets Prepared by Liquid Layering - Haoran Wang; Lin Han; Han Zeng; Mengyao Yu; Tian Yin; Yu Zhang; Haibing He; Jingxin Gou; Xing Tang (Pharmaceutical Research, 2025)

Correction to: Distinct expression of three estrogen receptors in response to bisphenol A and nonylphenol in male Nile tilapias (Oreochromis niloticus) - Weiren Huang; Yong Zhang; Xiaoping Jia; Xilan Ma; Shuisheng Li; Yun Liu; Pei Zhu; Danqi Lu; Huihong Zhao; Wenna Luo; Shibai Yi; Xiaochun Liu; et al. (Fish Physiology and Biochemistry, 2025)

Experimental and simulation study of pounding tuned mass damper on jumper flow induced vibration - Shanying Lin; Shengyan Pan; Wenhua Li; Haoran Ye; Guangzhao Li (Ocean Engineering, 2025)

Three-dimensional ordered macroporous nitrogen-doped carbon for efficient adsorption of flavonoids from plant extraction - Chuanmao Li; Wenyuan Lyu; Ruiting Lin; Haoran Liu; Yingfei Wang; Datong Chen; Fengliang Wang; Yingwei Li (Chemical Engineering Journal, 2025)

Air-sea CO2 exchange in the western Pacific influenced by monsoon and giant diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Journal of Asian Earth Sciences, 2024)

Effects of core soil microbial taxa on soil carbon source utilization under different long-term fertilization treatments in Ultisol - Haoran Mao; Guilong Li; Ke Leng; Luyuan Sun; Kailou Liu; Yongxin Lin; Jia Liu; Xingjia Xiang (Soil Ecology Letters, 2024)

Pure water and resource recovery from municipal wastewater using high-rate activated sludge, reverse osmosis, and mainstream anammox: A pilot scale study - Haoran Zhao; Yu Zhou; Lianpei Zou; Chihao Lin; Jianyong Liu; Yu-You Li (Water Research, 2024)

Biochar confers significant microbial resistance to ammonia toxicity in n-caproic acid production - Benteng Wu; Richen Lin; Jing Gu; Haoran Yuan; Jerry D. Murphy (Water Research, 2024)

Comparative study of dynamic characteristics between a FHAWT and a helical type FVAWT - Wanru Deng; Liqin Liu; Zihe Lin; Zhiming Yuan; Yan Li; Dongsheng Liu; Haoran Li; Ying Guo (Ocean Engineering, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Low voltage electrostatic field combined with ice-temperature to improve the quality of litchi during storage - Junping Zhou; Jijun Wu; Haoran Liu; Xian Lin; Lina Cheng; Chuyuan Li; Shaoquan Weng; Min Zhao; Yujuan Xu; Jing Wen (Food Research International, 2024)

Experimental Study on the Classification and Evolution of the Tip Cavitation Morphology in Axial Waterjet Pumps with Two Different Blade Numbers - Xi Shen; Haoran Wu; Gang Yang; Rui Tang; Chenxin Chang; Bin Xu; Suben Lin; Desheng Zhang (Journal of Marine Science and Engineering, 2024)
Tip leakage flow and induced unstable cavitation can significantly damage the performance of axial waterjet pumps. This study investigated the impact of blade numbers on cavitating conditions in an axial waterjet pump by conducting tests of performance characteristics and high-speed photography experiments on three-blade and four-blade impellers. The results showed that the critical cavitation number σc of the three-blade impeller was larger, while the four-blade impeller flow pattern deteriorated more rapidly after σc. Various cavitation structures in the tip region were observed under different conditions, including clearance cavitation, shear layer cavitation, tip leakage vortex cavitation, and suction-side-perpendicular cavitating vortices (SSPCVs). Tip cavitation maps of the test impellers were drawn based on the flow rate coefficient and cavitation number variation. The three-blade impeller exhibited a wider range of severe cavitation, particularly with an increased occurrence of SSPCVs. With the cavitation number and flow rate coefficient decreased, the SSPCV generated from triangular cavitation cloud shedding presented an increased trend in scale and quantity. Conversely, in the case of the four-blade impeller, SSPCVs were often disrupted by the adjacent blade during migration and interfered with the tip cavitation in the neighboring flow passage.

Effects of microplastics and combined pollution of polystyrene and di-n-octyl phthalate on photosynthesis of cucumber (Cucumis sativus L.) - Haoran Zhuang; Zhenxia Li; Menglin Wang; Bo Liu; Yiwen Chu; Ziyu Lin (Science of The Total Environment, 2024)

Comparative investigation on composting and pyrolysis of swine manure: Heavy metals transformation, nitrogen immobilization and integrated environmental risk assessment - Fengxiao Zhao; Rui Shan; Hongyuan Chen; Dong Liang; Xianhai Zeng; Lu Lin; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2024)

Primary productivity recovery and shallow-water oxygenation during the Sturtian deglaciation in South China - Xubin Wang; Lin Dong; Haoran Ma; Xianguo Lang; Ruimin Wang (Global and Planetary Change, 2024)

Voltage recovery from frozen microbial fuel cells in the laboratory and outdoor field reactors - Chunyang Lin; Haoran Liang; Xiaojing Yang; Jingjing Zhan; Qiao Yang (Science of The Total Environment, 2024)

Construction of 2D porous g-C3N4 by steam reforming with the introduction of Fe clusters forming Fe-Nx to enhance photo-Fenton catalytic activity - Xiaotong Tian; Yuting Lin; Haoran Xu; Xingxing Gao; Weicheng Wu; Ailing Wang; Xiaoshun Zhang; Jian Wang; Wenqing Yao (Journal of Water Process Engineering, 2024)

Visible light irradiation enhanced sulfidated zero-valent iron/peroxymonosulfate process for organic pollutant degradation - Jialu Xu; Hao Cheng; He Zhang; Chengyou Sun; Haoran Tian; Jikun Yang; Yingxin Ding; Xuan Lin; Ping Wang; Chao Huang (Environmental Research, 2024)

Tree species classification based on PointNet++ deep learning and true- colour point cloud - Haoran Liu; Hao Zhong; Wenshu Lin; Jinzhuo Wu (International Journal of Remote Sensing, 2024)

Effective or useless? Assessing the impact of park entrance addition policy on green space services from the 15-min city perspective - Qinyu Cui; Lin Tan; Haoran Ma; Xuelin Wei; Shengao Yi; Dan Zhao; Huiyuan Lu; Peiqun Lin (Journal of Cleaner Production, 2024)

3D Effect and countermeasure of 2D geoelectrical imaging of a subsurface linear structure - Yin-Chun Hung; Haoran Wang; Po-Lin Wu; Hsin-Chang Liu; Chih-Ping Lin (Engineering Geology, 2024)

Phosphate-based ionic liquids for advanced interface modification in perovskite photovoltaics: Novel insights for ionic liquid molecule design - Guo Yang; Fei Wang; Chao Zhou; Yonggui Sun; Taomiao Wang; Qiannan Li; Yongjun Li; Xiao Liang; Xianfang Zhou; Quanyao Zhu; Haoran Lin; Hanlin Hu (Chemical Engineering Journal, 2024)

Effect of urban street canyon aspect ratio on fire-induced air pollutants dispersion under cross wind - Shengzhong Zhao; Junhao Yu; Haoran Yang; Imad Obadi; Tiantian Xu; Fei Wang; Lin Xu; Wenjun Lei (Atmospheric Pollution Research, 2024)

IFNγ modulates the innate immune response via Toll-like receptors in green-spotted pufferfish (Tetraodon nigroviridis) - Wenjie Lai; Qinxi Dai; Zhenjiang Zou; Ziyi Wu; Ting Wang; Xue Yu; Yakang Song; Jingpeng Hou; Yuyou Lu; Dingrui Liu; Haoran Lin; Yong Zhang; et al. (Aquaculture International, 2024)

TBC1D10B promotes tumor progression in colon cancer via PAK4‑mediated promotion of the PI3K/AKT/mTOR pathway - Xiao-Jv Chi; Yi-Bei Song; Haoran Zhang; Li-Qiang Wei; Yong Gao; Xue-Jing Miao; Shu-Ting Yang; Chun-Yu Lin; Dong Lan; Xiquan Zhang (Apoptosis, 2024)

East Asian Winter Monsoon and enhanced stratification in the western Pacific promoted giant marine diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Quaternary Science Reviews, 2024)

Simultaneous Cu(II)-EDTA decomplexation and Cu(II) recovery using integrated contact-electro-catalysis and capacitive deionization from electroplating wastewater - Xiaoyan Shen; Shiyong Wang; Lin Zhao; Haoran Song; Wei Li; Changping Li; Sihao Lv; Gang Wang (Journal of Hazardous Materials, 2024)

Resource utilization of coal chemical waste salt by bipolar membrane electrodialysis with thermal pretreatment - Haoran Xin; Xindi Chen; Songwei Lin; Haiping Luo; Yingjie Cao; Chuyang Y. Tang; Guangli Liu (Desalination, 2024)

Effect of faba bean Vicia faba L. water/alcohol extract on growth performance, antioxidant capacity, textural properties, and collagen deposition in the swim bladder of juvenile Nibea coibor - Haoji Guo; Guoquan Liu; Mengdu Tian; Chunsheng Liu; Haoran Zhang; Shuqi Wang; Xiaobo Wen; Fan Lin (Fish Physiology and Biochemistry, 2024)

Airborne ARGs/MGEs from two sewage types during the COVID-21: Population, microbe interactions, cytotoxicity, formation mechanism, and dispersion - Yanjie Wang; Song Zhang; Lin Li; Qiao Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Jian Wu; Linlin Hua (Water Research, 2024)

Sex and age disparities in multi-metal mixture exposure and cognitive impairment in urban elderly individuals: The mediation effect and biological function of metabolites - Qingzhi Hou; Jiujing Lin; Xiangsheng Xue; Yuchen Zhang; Zhanhui Qiu; Haoran Zhang; Jia Li; Harry Wang; Shuping Zhang; Zhigang Yao; Xiaomei Li; Fei Wang; et al. (Science of The Total Environment, 2024)

Spatiotemporal distribution, interactions and toxic effect of microorganisms and ARGs/MGEs from the bioreaction tank in hospital sewage treatment facility - Yanjie Wang; Song Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Lin Li; Linlin Hua (Science of The Total Environment, 2024)

Oxidized cellulose-filled double thermo/pH-sensitive hydrogel for local chemo-photothermal therapy in breast cancer - Zijian Zhang; Haoran Cui; Xin Wang; Jie Liu; Guangchun Liu; Xin Meng; Song Lin (Carbohydrate Polymers, 2024)

Experimental and numerical investigation on the interaction between rogue waves and a KVLCC2 in head sea - Jiaqian Wang; Hao Qin; Weiyi Zhang; Haoran Zhang; Lin Mu (Ocean Engineering, 2024)

Mediation of the agricultural water rebound effect through climate conditions and types of crop mix - Ying Chai; Lin Li; Zilong Ma; Haoran Zhang; Su Pan; Jieqi Zhou (Irrigation and Drainage, 2024)
The water rebound effect is recognized as an impediment to irrigation efficiency enhancement for saving water. This study foregrounds climate conditions and crop mix as two important contexts influencing the relationship between irrigation efficiency and water use (the water rebound effect). Considering China as our study area for conducting an empirical analysis of this relationship, we used the data envelopment analysis (DEA)–Malmquist method and econometric models to examine their impact on the water rebound effect. The results of the analysis revealed that the water rebound effect in China is 69.1%, with humid conditions being the main factor moderating an increase in it. Whereas cash crop cultivation is associated with water conservation under drought conditions, this is not the case under humid conditions. These findings suggest that given the prioritization of food security, policies to reduce cash crops should be introduced, thereby mediating the water rebound effect.

Load Assessment Method for Multi-Layer Oceanographic Winch with Synthetic Fibre Ropes Based on Non-Rotation Symmetric Cylindrical Model - Haoran Ye; Wenhua Li; Shanying Lin; Qingtao Lv; Dinghua Zhang (Journal of Marine Science and Engineering, 2024)
Offshore winches are crucial in marine engineering, particularly in marine scientific research and deep-sea exploration. The use of fibre ropes presents significant opportunities for the weight reduction of winches as a consequence of the low length–strength ratio and characteristics of corrosion resistance. Nonetheless, a challenge arises in underestimating the stress load levels in load assessments of multi-layer winch systems using synthetic fibre ropes. Traditional computational methods reliant on symmetrically rotational models fall short in accurately predicting and assessing practical applications. This paper introduces a finite element analysis model based on a non-rotationally symmetric approach with four surfaces subjected to various radial pressure on account of the deformation of the fibre ropes. In the design model, sixteen stress detection paths have been incorporated to identify and confirm non-linear stresses. The outcomes of the finite element simulations have been compared with experimental results with two synthetic fibre ropes, each with distinct deformation characteristics utilised. The findings demonstrate that the application of the model aligns well with experimental results, showcasing its relevance and practical value in real-world scenarios. Precise theoretical calculations and experimental validation are pivotal to ensuring that equipment reliability and safety are maintained alongside the pursuit of light-weighting.

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Fatigue degradation of wind turbines considering dynamic wake meandering effects - Jian Zhang; Haoran Zuo; Songye Zhu; Jun Yang; Lin Lu (Engineering Structures, 2024)

Investigating the planning efficiency of species richness- and complementarity-based algorithms in data deficient areas - Jin Ye; Feiling Yang; Jinming Hu; Feng Liu; Yiting Wang; Jian Zhou; Jingwen Lin; Jianlin Wang; Xiujun Zhang; Qiying Wang; Haoran Chen; Ruidong Wu (Biological Conservation, 2024)

MAX-DOAS and in-situ measurements of aerosols and trace gases over Dongying, China: Insight into ozone formation sensitivity based on secondary HCHO - Xiaojun Zheng; Zeeshan Javed; Cheng Liu; Aimon Tanvir; Osama Sandhu; Haoran Liu; Xiangguang Ji; Chengzhi Xing; Hua Lin; Daolin Du (Journal of Environmental Sciences, 2024)

Linked mutations within the pathogenicity locus of Clostridioides difficile increase virulence - Qianyun Lin; Zitong Li; Haoran Ke; Jiaxi Fei; Ting Zhang; Pu Wang; Ye Chen (Infectious Diseases, 2023)

Diversification of faunal exploitation strategy and human-climate interaction in Southern China and Southeast Asia during the last deglaciation - Yongxiu Lu; Feng Gao; Yiren Wang; Minmin Ma; Aifeng Zhou; Ruiliang Liu; Hiroki Kikuchi; Lele Ren; Qingfeng Shao; Lin Chen; Yongxiang Xu; Haoran Li; et al. (Quaternary Science Reviews, 2023)

Covalent organic frameworks for modulating crystallization kinetics in perovskite photovoltaics - Xiao Liang; Chaoqin Han; Fei Wang; Jiajun Wu; Xianfang Zhou; Haoran Lin; Xiaoyuan Liu; Quanyao Zhu; Gang Li; Hanlin Hu (Chemical Engineering Journal, 2023)

Transcriptional activation of membrane-related Toll-like receptor 5 through the NF-κB subunit p65 and Vibrio parahaemolyticus flagellin in orange-spotted grouper (Epinephelus coioides) - Xue Yu; Liangge He; Songze Gao; Yuqi Liu; Jiachang Xu; Yulin Zhao; Haoran Lin; Yong Zhang; Danqi Lu (Aquaculture, 2023)

Co-pyrolysis of textile dyeing sludge/litchi shell and CaO: Immobilization of heavy metals and the analysis of the mechanism - Danni Li; Rui Shan; Jing Gu; Yuyuan Zhang; Xianhai Zeng; Lu Lin; Haoran Yuan; Yong Chen (Waste Management, 2023)

Assessment of CO2 fracturing in China's shale oil reservoir: Fracturing effectiveness and carbon storage potential - Wenrui Shi; Ling Zhu; Meiyu Guo; Zisang Huang; Ganlu Wang; Lijie Lin; Li He; Yong Liao; Haoran He; Junshi Gong (Resources, Conservation and Recycling, 2023)

Dual-layer drug release system based on ureteral stents inhibits the formation of ureteral stricture - Zhiduan Cai; Wenjun Luo; Haoquan Zhuang; Congling Ren; Xiaolin Pan; Yuyu Xu; Haoran Wang; Xiezhao Li; Yaoji Yuan; Rui Zhu; Xiangyu Zhan; Lin Jin; et al. (Chemical Engineering Journal, 2023)

Dietary hydroxyproline promotes collagen deposition in swim bladder through regulating biosynthesis of amino acid: In-vitro and in-vivo investigations in Nibea coibor - Haoji Guo; Qianhui Zhang; Xin Liu; Haoran Zhang; Shuqi Wang; Xiaobo Wen; Fan Lin (Aquaculture, 2023)

Dual photoelectrodes activate oxygen evolution and oxygen reduction reactions enabling a high-performance Zn-air battery and an efficient solar energy storage - Jia You; Bingqing Zhang; Xianlong Wang; Haoran Zhang; Lanlan Huang; Lihua He; Nanxin Li; Yichen Chang; Shiwei Lin (Chemical Engineering Journal, 2023)

Secondary organic aerosols in PM2.5 on a coastal island in southeastern China: Impact of atmospheric process and biomass burning - Naihua Chen; Jianyong You; Jie Huang; Yuxiang Yang; Haoran Lin; Xin Qi; Xiaoxiao Chen; Yushan Yang; Baoye Hu (Atmospheric Environment, 2023)

Lead-imprinted polyvinylidene fluoride membrane for selective removal of lead from contaminated water: material fabrication, filtration application, and mechanism study - Dandan Zhao; Chen Fu; Sudan Lin; Yongzhi Xu; Haoran He; Siyuan Liu; Xueqing Shi (Environmental Science and Pollution Research, 2023)

Experimental evaluation of dimension-stable synthetic fibre rope under investigation of spooling test on the multilayer winch drum - Haoran Ye; Wenhua Li; Hongxin Zhang; Shanying Lin; Dinghua Zhang; Yangyuan Ge; Zehua Li (Ocean Engineering, 2023)

NMR-tracking for 15,16-seco-cycloartane triterpenes from Cimicifuga acerina - Liwu Lin; Haoran Zhou; Luan Wen; Abdulbaset Al-Romaima; Xingrong Peng; Minghua Qiu (Phytochemistry, 2023)

Feed-in tariffs and the carbon emission trading scheme under China's peak emission target: A dynamic CGE analysis for the development of renewable electricity - Lingli Qi; Xinyue Lin; Xile Shi; Yongqiang Zhang; Haoran Pan; Basil Sharp (Journal of Environmental Management, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Irisin attenuates ethanol-induced behavioral deficits in mice through activation of Nrf2 and inhibition of NF-κB pathways - Xi Jiang; Qizhi Yan; Wendie Lao; Qian Lin; Haoran Cao; Lei Chen; Jin Chen; Xuefeng Yu; Fuhe Liu (Metabolic Brain Disease, 2023)

Novel Y2O3 based calcium-alginate beads for highly selective adsorption of phosphate from aqueous solution - Sudan Lin; Yongzhi Xu; Chen Fu; Haifeng Zhang; Qiaoping Kong; Haoran He; Siyuan Liu; Xueqing Shi; Dandan Zhao (Environmental Science and Pollution Research, 2023)

Molecular Characterization of U6 Promoters from Orange-Spotted Grouper (Epinephelus coioides) and Its Application in DNA Vector-Based RNAi Technology - Fengying Yan; Xinxun Xiao; Chen Long; Lin Tang; Chongwei Wang; Mingqing Zhang; Jin Zhang; Haoran Lin; Hai Huang; Yong Zhang; Shuisheng Li (Marine Biotechnology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Effects of salinity on growth, physiology, biochemistry and gut microbiota of juvenile grass carp (Ctenopharyngodon idella) - Dingrui Liu; Zhuowei Zhang; Yikun Song; Jiayu Yang; Yuyou Lu; Wenjie Lai; Ziyi Wu; Dandan Zhao; Haoran Lin; Yong Zhang; Jin Zhang; Shuisheng Li (Aquatic Toxicology, 2023)

Genome-wide association analysis of Fusarium crown rot resistance in Chinese wheat landraces - Shuai Hou; Yu Lin; Shifan Yu; Ning Yan; Hao Chen; Haoran Shi; Caixia Li; Zhiqiang Wang; Yaxi Liu (Theoretical and Applied Genetics, 2023)

Genome-wide identification and characterization of circRNAs in wheat tiller - Fangkun Wu; Zhiqiang Wang; Wanlin Zhou; Yan Liu; Haoran Shi; Xiangjian Gou; Haojie Li; Yu Lin; Caixia Li; Yaxi Liu (Theoretical and Applied Genetics, 2023)

Full-length transcriptome sequence and SSR marker development for genetic diversity research in yellowfin seabream Acanthopagrus latus - Jin Zhang; Jinmei Liu; Chong Han; Cheng Peng; Yong Li; Junhong Xia; Yong Zhang; Shuisheng Li; Haoran Lin (Journal of Oceanology and Limnology, 2023)

Nano-Fe3O4 coated on carbon monolith for anode enhancement in microbial fuel cells - Yini Chen; Fan Zhao; Yu Pu; Xiangyu Lin; Haoran Yin; Xinhua Tang (Journal of Environmental Chemical Engineering, 2023)

Enhanced adsorption of bio-oil on activated biochar in slurry fuels and the adsorption selectivity - Shanshan Yan; Haoran Chen; Haonan Zhu; Zixiang Lin; Gang Wu; Wenran Gao; Hong Zhang; Xun Hu; Junjie Zhang; Shu Zhang; Shoujun Zhang; Yinlong Wu (Fuel, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Effects of ambient pressure on fire-induced buoyancy driven plume dispersion and re-entrainment behavior in a street canyon - Shengzhong Zhao; Haoran Yang; Tiantian Xu; Fei Wang; Chaorui Li; Lin Xu (Atmospheric Pollution Research, 2023)

The preliminary study of exosomes derived from thymosin beta 4-treated adipose-derived stem cells in fat grafting - Wandi Li; Yan Yang; Xiaoyu Zhang; Yan Lin; Haoran Li; Yu Yao; Dali Mu (Genes & Genomics, 2023)

New insights into the carbon cycle and depositional models of the Eocene saline lake, Jianghan basin, China - Ren Wei; Haoran Ma; Zhijun Jin; Tianyu Wang; Chi Zhang; Yuhan Wang; Lin Dong (Marine and Petroleum Geology, 2023)

Metal-organic framework nanocrystals enabled efficient and durable two-step perovskite photovoltaics - Xiao Liang; Kang Zhou; Dawei Duan; Fei Wang; Chuangye Ge; Xianfang Zhou; Mingjian Yuan; Yumeng Shi; Haoran Lin; Quanyao Zhu; Gang Li; Hanlin Hu (Chemical Engineering Journal, 2023)

Growth and physiological–biochemical characteristics of cucumber (Cucumis sativus L.) in the presence of different microplastics - Haoran Zhuang; Xiaoyi Liu; Han Ma; Ruijing Li; Bo Liu; Ziyu Lin; Zhenxia Li (Arabian Journal of Geosciences, 2023)

Molecular cloning and characterization of NLRX1 from orange-spotted grouper (Epinephelus coioides) as a mediator of ROS production through its LRR domains - Xu Ding; Yaosi Liang; Qinghua Hou; Shuisheng Li; Wan Peng; Ruozhu Li; Haoran Lin; Yong Zhang; Danqi Lu (Aquaculture, 2023)

Laminar flame speeds of cyclic hydrocarbon fuels: Effect of unsaturation - Hu Liu; Wenjun Lin; Qianqian Li; Haoran Zhao; Zuohua Huang (Fuel, 2023)

The linear behavior of the joint initial-boundary-value predictability of the climate system - Jianlin Yong; Shaoqing Zhang; Zhengyu Liu; Yang Gao; Lixin Wu; Jianping Li; Lv Lu; Yingjing Jiang; Xiaolin Yu; Mingkui Li; Haoran Zhao; Xiaopei Lin (Climate Dynamics, 2023)

Effects of hyperosmotic stress on the intestinal microbiota, transcriptome, and immune function of mandarin fish (Siniperca chuatsi) - Haofeng Ouyang; Niuniu Deng; Jiachang Xu; Jingjun Huang; Chong Han; Dingrui Liu; Shiyan Liu; Baohua Yan; Linqiang Han; Shuisheng Li; Guifeng Li; Jin Zhang; et al. (Aquaculture, 2023)

Screening and characterization of X chromosome-specific markers in mandarin fish (Siniperca chuatsi) - Shiyan Liu; Chong Han; Jingjun Huang; Qiaoying Zhu; Dingrui Liu; Linqiang Han; Shuisheng Li; Guifeng Li; Haoran Lin; Yong Zhang (Aquaculture, 2023)

A multi-modal brain–computer interface based on threshold discrimination and its application in wheelchair control - Enzeng Dong; Haoran Zhang; Lin Zhu; Shengzhi Du; Jigang Tong (Cognitive Neurodynamics, 2022)

Effect of straw biochar from different crops on growth and nutrient uptake by peach (Prunus davidiana) seedlings - Qin Liu; Haoran Zhang; Yan Wang; Jing Sun; Dong Chen; Meiyan Tu; Lijin Lin (Acta Physiologiae Plantarum, 2022)

An input–output structural decomposition analysis of changes in China’s renewable energy consumption - Xinyue Lin; Haoran Pan; Lingli Qi; Yi-Shuai Ren; Basil Sharp; Chaoqun Ma (Environmental Science and Pollution Research, 2022)

Fine mapping of the tiller inhibition gene TIN4 contributing to ideal plant architecture in common wheat - Zhiqiang Wang; Fangkun Wu; Xudong Chen; Wanlin Zhou; Haoran Shi; Yu Lin; Shuai Hou; Shifan Yu; Hong Zhou; Caixia Li; Yaxi Liu (Theoretical and Applied Genetics, 2022)

Identification of potential sex-related genes in Siniperca chuatsi - Qiaoying Zhu; Chong Han; Cheng Peng; Xingni Zhou; Chongwei Wang; Linqiang Han; Shuisheng Li; Guifeng Li; Haoran Lin; Yong Zhang (Journal of Oceanology and Limnology, 2021)

Physical interactions facilitate sex change in the protogynous orange‐spotted grouper, Epinephelus coioides - Jiaxing Chen; Cheng Peng; Jingjun Huang; Herong Shi; Ling Xiao; Lin Tang; Haoran Lin; Shuisheng Li; Yong Zhang (Journal of Fish Biology, 2021)
Sex change in teleost fishes is commonly regulated by social factors. In species that exhibit protogynous sex change, such as the orange‐spotted grouper Epinephelus coioides , when the dominant males are removed from the social group, the most dominant female initiates sex change. The aim of this study was to determine the regulatory mechanisms of socially controlled sex change in E. coioides . We investigated the seasonal variation in social behaviours and sex change throughout the reproductive cycle of E. coioides , and defined the behaviour pattern of this fish during the establishment of a dominance hierarchy. The social behaviours and sex change in this fish were affected by season, and only occurred during the prebreeding season and breeding season. Therefore, a series of sensory isolation experiments was conducted during the breeding season to determine the role of physical, visual and olfactory cues in mediating socially controlled sex change. The results demonstrated that physical interactions between individuals in the social groups were crucial for the initiation and completion of sex change, whereas visual and olfactory cues alone were insufficient in stimulating sex change in dominant females. In addition, we propose that the steroid hormones 11‐ketotestosterone and cortisol are involved in regulating the initiation of socially controlled sex change.

Maternal Separation-Induced Histone Acetylation Correlates with BDNF-Programmed Synaptic Changes in an Animal Model of PTSD with Sex Differences - Haoran Sun; Xianqiang Zhang; Yujia Kong; Luping Gou; Bo Lian; Yanyu Wang; Li Jiang; Qi Li; Hongwei Sun; Lin Sun (Molecular Neurobiology, 2021)

Correction to: A Chromosomal-scale Reference Genome of the Kelp Grouper Epinephelus moara - Qian Zhou; Haoyang Gao; Hao Xu; Haoran Lin; Songlin Chen (Marine Biotechnology, 2021)

A Chromosomal-scale Reference Genome of the Kelp Grouper Epinephelus moara - Qian Zhou; Haoyang Gao; Hao Xu; Haoran Lin; Songlin Chen (Marine Biotechnology, 2021)

Comparison of the Nutritional Quality of Three Edible Tissues from Precocious and Normal Adult Female Chinese Mitten Crabs ( Eriocheir sinensis ) - Huafeng Cheng; Haoran Wu; Feng Liang; Mengtian Ge; Shaotong Jiang; Lin Lin; Jianfeng Lu (Journal of Aquatic Food Product Technology, 2021)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

The relationship between solar-induced fluorescence and gross primary productivity under different growth conditions: global analysis using satellite and biogeochemical model data - Haoran Zhou; Dun Wu; Yi Lin (International Journal of Remote Sensing, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Natural sex change in mature protogynous orange‐spotted grouper ( Epinephelus coioides ): gonadal restructuring, sex hormone shifts and gene profiles - Cheng Peng; Qing Wang; Herong Shi; Jiaxing Chen; Shuisheng Li; Huihong Zhao; Haoran Lin; Jianchun Yang; Yong Zhang (Journal of Fish Biology, 2020)
Sexual patterns of teleosts are extremely diverse and include both gonochorism and hermaphroditism. As a protogynous hermaphroditic fish, all orange‐spotted groupers ( Epinephelus coioides ) develop directly into females, and some individuals change sex to become functional males later in life. This study investigated gonadal restructuring, shifts in sex hormone levels and gene profiles of cultured mature female groupers during the first (main) breeding season of 2019 in Huizhou, China (22° 42′ 02.6″ N, 114° 32′ 10.1″ E). Analysis of gonadal restructuring revealed that females with pre‐vitellogenic ovaries underwent vitellogenesis, spawning and regression and then returned to the pre‐vitellogenic stage in the late breeding season, at which point some changed sex to become males via the intersex gonad stage. A significant decrease in the level of serum 17 β ‐estradiol (E2) was observed during ovary regression but not during sex change, whereas serum 11‐ketotestosterone (11‐KT) concentrations increased significantly during sex change with the highest concentration in newly developed males. Consistent with serum hormone changes, a significant decrease in cyp19a1a expression was observed during ovary regression but not during sex change, whereas the expression of cyp11c1 and hsd11b2 increased significantly during sex change. Interestingly, hsd11b2 but not cyp11c1 was significantly upregulated from the pre‐vitellogenic ovary stage to the early intersex gonad stage. These results suggest that a decrease in serum E2 concentration and downregulation of cyp19a1a expression are not necessary to trigger the female‐to‐male transformation, whereas increased 11‐KT concentration and upregulation of hsd11b2 expression may be key events for the initiation of sex change in the orange‐spotted grouper.

Effects of dietary proline on growth, physiology, biochemistry and TOR pathway-related gene expression in juvenile spotted drum Nibea diacanthus - Hua Rong; Fan Lin; Yunlong Zhang; Jun Yu; Chuanqi Yu; Haoran Zhang; Jude Juventus Aweya; Xiaobo Wen (Fisheries Science, 2020)

Influence of humic acid and its different molecular weight fractions on sedimentation of nanoscale zero-valent iron - Yanan Wu; Haoran Dong; Lin Tang; Long Li; Yaoyao Wang; Qin Ning; Bin Wang; Guangming Zeng (Environmental Science and Pollution Research, 2020)

Transcriptomic Analysis Revealed the Regulatory Mechanisms of Oocyte Maturation and Hydration in Orange-Spotted Grouper (Epinephelus coioides) - Lin Tang; Jiaxing Chen; Zhifeng Ye; Mi Zhao; Zining Meng; Haoran Lin; Shuisheng Li; Yong Zhang (Marine Biotechnology, 2019)

EGFR Mimotope Reduces the Expression of LYVE-1 in the Intestine from the M3R Immunized Mice - Haoran Yuan; Changhong Li; Jianying Niu; Lin Yang (International Journal of Peptide Research and Therapeutics, 2019)

Socially controlled male‐to‐female sex reversal in the protogynous orange‐spotted grouper, Epinephelus coioides - Jiaxing Chen; Ling Xiao; Cheng Peng; Zhifeng Ye; Dengdong Wang; Yuqing Yang; Haifa Zhang; Mi Zhao; Shuisheng Li; Haoran Lin; Yong Zhang (Journal of Fish Biology, 2019)
Socially controlled sex change in teleosts is a dramatic example of adaptive reproductive plasticity. In many cases, the occurrence of sex change is triggered by a change in the social context, such as the disappearance of the dominant individual. The orange‐spotted grouper Epinephelus coioides is a typical protogynous hermaphrodite fish that changes sex from female to male and remains male throughout its life span. In this study, male‐to‐female sex reversal in male Epinephelus coioides was successfully induced by social isolation. The body length and mass, gonadal change, serum sex steroid hormone levels and sex‐related gene expression patterns during the process of socially controlled male‐to‐female sex reversal in E. coioides were systematically examined. This report investigates the physiological mechanisms of the socially controlled male‐to‐female sex reversal process in a protogynous hermaphrodite grouper species. The results enable us to study the physiological control of sex change, not only from female to male, but also from male to female.

Stability Analysis of Clastic Rock Slope with Mudstone Interlayer Under Rainfall Infiltration - Yingzi Xu; Jian Li; Haoran Fan; Lihua Chen; Yanlin Zhao; Lin Li (Geotechnical and Geological Engineering, 2017)

Antiplatelet Strategies and Outcomes in Patients with Noncardioembolic Ischemic Stroke from a Real-World Study with a Five-Year Follow-Up - Huimin Xu; Yanting Ping; Haoran Lin; Ping He; Wenlu Li; Haibin Dai (Translational Stroke Research, 2017)

Copy Number Variations in Tilapia Genomes - Bi Jun Li; Hong Lian Li; Zining Meng; Yong Zhang; Haoran Lin; Gen Hua Yue; Jun Hong Xia (Marine Biotechnology, 2017)

Microsatellite analysis of the genetic relationships between wild and cultivated giant grouper in the South China Sea - QING WANG; XIANG WANG; ZHENZHEN XIE; YIQI LI; LING XIAO; CHENG PENG; HAIFA ZHANG; SHUISHENG LI; YONG ZHANG; HAORAN LIN (Journal of Genetics, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The Longmala and Mengya’a skarn Pb–Zn deposits, Gangdese region, Tibet: evidence from U–Pb and Re–Os geochronology for formation during early India–Asia collision - Liqiang Wang; Juxing Tang; Jun Deng; Haoran Kang; Xin Lin; Wenbin Cheng; Zhuang Li; Zhi Zhang (International Geology Review, 2015)

Different senescent HDPE pipe-risk: brief field investigation from source water to tap water in China (Changsha City) - Jing Tang; Lin Tang; Chang Zhang; Guangming Zeng; Yaocheng Deng; Haoran Dong; Jingjing Wang; Yanan Wu (Environmental Science and Pollution Research, 2015)

Cloning, expression, and ligand-binding characterization of two neuropeptide Y receptor subtypes in orange-spotted grouper, Epinephelus coioides - Fei Wang; Weimin Chen; Haoran Lin; Wensheng Li (Fish Physiology and Biochemistry, 2014)

Arbuscular mycorrhizae improve low temperature tolerance in cucumber via alterations in H2O2 accumulation and ATPase activity - Airong Liu; Shuangchen Chen; Rui Chang; Dilin Liu; Haoran Chen; Golam Jalal Ahammed; Xiaomin Lin; Chaoxing He (Journal of Plant Research, 2014)

Development and characterization of 13 novel microsatellite loci in a threatened reef fish, humpback grouper (Cromileptes altivelis) - Yu Wang; Guohua Chen; Feng Yan; Haoran Lin; Jian Luo (Conservation Genetics Resources, 2014)

Effects of cysteamine on mRNA levels of growth hormone and its receptors and growth in orange-spotted grouper (Epinephelus coioides) - Yun Li; Xiaochun Liu; Yong Zhang; Xilan Ma; Haoran Lin (Fish Physiology and Biochemistry, 2013)

Molecular characterization and expression pattern of insulin-like growth factor binding protein-3 (IGFBP-3) in common carp, Cyprinus carpio - Wenbo Chen; Haoran Lin; Wensheng Li (Fish Physiology and Biochemistry, 2012)

The second prolactin receptor in Nile tilapia (Oreochromis niloticus): molecular characterization, tissue distribution and gene expression - Yong Zhang; Zijie Long; Yangyuan Li; Shibai Yi; Yu Shi; Xilan Ma; Weiren Huang; Danqi Lu; Pei Zhu; Xiaochun Liu; Zining Meng; Xigui Huang; et al. (Fish Physiology and Biochemistry, 2010)

Distinct expression of three estrogen receptors in response to bisphenol A and nonylphenol in male Nile tilapias (Oreochromis niloticus) - Weiren Huang; Yong Zhang; Xiaoping Jia; Xilan Ma; Shuisheng Li; Yun Liu; Pei Zhu; Danqi Lu; Huihong Zhao; Wenna Luo; Shibai Yi; Xiaochun Liu; et al. (Fish Physiology and Biochemistry, 2010)

Foreword - Lin Haoran (Fish Physiology and Biochemistry, 2010)

Growth hormone and two forms of insulin-like growth factors I in the giant grouper (Epinephelus lanceolatus): molecular cloning and characterization of tissue distribution - Haiyan Dong; Lingxian Zeng; Da Duan; Haifa Zhang; Yunxin Wang; Wensheng Li; Haoran Lin (Fish Physiology and Biochemistry, 2010)

The endocrine regulation network of growth hormone synthesis and secretion in fish: Emphasis on the signal integration in somatotropes - WenSheng Li; HaoRan Lin (Science China Life Sciences, 2010)

An overview of dry-wet climate variability among monsoon-westerly regions and the monsoon northernmost marginal active zone in China - Weihong Qian; Ting Ding; Haoran Hu; Xiang Lin; Aimin Qin (Advances in Atmospheric Sciences, 2009)

Rat Ghrelin Stimulates GH Release and GH mRNA Expressionin the Pituitary of Orange-spotted Grouper, Epinephelus Coioides - Xueqin Ran; Wensheng Li; Haoran Lin (Fish Physiology and Biochemistry, 2004)